2001
DOI: 10.1051/0004-6361:20010203
|View full text |Cite
|
Sign up to set email alerts
|

Non-axisymmetric accretion on the classical TTS RW Aur A

Abstract: Abstract. High-resolution spectroscopic monitoring of the exceptionally active classical T Tauri star (CTTS) RW Aur A was carried out in three seasons of 1996, 1998 and 1999 with simultaneous B, V photometry. The high quality spectra revealed a multicomponent structure of the spectrum, which includes: 1) a veiled photospheric spectrum of a K1-K4 star, 2) broad emission lines of neutrals and ions, 3) narrow emission lines of He i and He ii, 4) red-shifted accretion features of many lines, 5) shell lines at abou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
153
4
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(183 citation statements)
references
References 28 publications
24
153
4
2
Order By: Relevance
“…Our calculations based on the high resolution module give a luminosity of (1.5 ± 0.3) × 10 28 erg s −1 . RW Aur is an optically bright T Tauri star; Petrov et al (2001) suggested that this is a binary system. The secondary, RW Aur B, is located 1.…”
Section: Discussionmentioning
confidence: 99%
“…Our calculations based on the high resolution module give a luminosity of (1.5 ± 0.3) × 10 28 erg s −1 . RW Aur is an optically bright T Tauri star; Petrov et al (2001) suggested that this is a binary system. The secondary, RW Aur B, is located 1.…”
Section: Discussionmentioning
confidence: 99%
“…RW Aur might be a multiple hierarchical system, although this is not clear. RW Aur A is a suspected spectroscopic binary (Petrov et al 2001). Another component, which was resolved very close to the secondary (Ghez et al 1993), was probably a false detection (White & Ghez 2001).…”
Section: Introductionmentioning
confidence: 93%
“…These signatures are prominent in RW Aur A and indicate that the accretion from a circumstellar disk is heavy and variable (e.g. Petrov et al 2001a; hereafter called P2001). RW Aur is a visual binary with a separation of 1.4 , where the faint component B is a weak-line TTS, a PMS star with little or no evidence of accretion.…”
Section: Introductionmentioning
confidence: 99%
“…Gahm et al (1993) and R2013. However, colour changes with periods of 2.7 to 2.8 days have been reported (Petrov et al 2001b, which is close to half the expected rotational period of about 5.6 days as determined from variations of the longitudal magnetic field of the star (Dodin et al 2012). The star becomes redder with decreasing brightness, and the frequent drops in brightness from an average level of V ≈ 10.4 appears to be, at least in part, related to variable foreground extinction (e.g.…”
Section: Introductionmentioning
confidence: 99%